2008
DOI: 10.1016/j.ygeno.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of osmotic stress response gene in Arabidopsis thaliana

Abstract: In this paper, we present a cis-regulatory element based computational approach to genome-wide identification of genes putatively responding to various osmotic stresses in Arabidopsis thaliana. The rationale of our method is that gene expression is largely controlled at the transcriptional level through the interactions between transcription factors and cis-regulatory elements. Using cis-regulatory motifs known to regulate osmotic stress response, we therefore built an artificial neural network model to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…We have also found that the mutant plants grown under high illumination compensated for the absence of α-CA4 and for reduced NPQ by the increase in the contents of both PsbS protein and the violaxanthin cycle components, the latter accompanied by an increase in violaxanthin deepoxidase activity [13]. In addition, α-ca4 gene was found among the genes that change the expression level under osmotic stress [136]. The content of α-ca4 gene transcripts became an order of magnitude higher in conditions of drought stress (Rudenko et al, in preparation).…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 63%
“…We have also found that the mutant plants grown under high illumination compensated for the absence of α-CA4 and for reduced NPQ by the increase in the contents of both PsbS protein and the violaxanthin cycle components, the latter accompanied by an increase in violaxanthin deepoxidase activity [13]. In addition, α-ca4 gene was found among the genes that change the expression level under osmotic stress [136]. The content of α-ca4 gene transcripts became an order of magnitude higher in conditions of drought stress (Rudenko et al, in preparation).…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 63%
“…RAHS-14 expressed more senescence-related genes, whereas we found that in Vagad, genes related to alcohol dehydrogenase and late embryogenesis protein 5 was expressed at a higher level (Additional files 5 and 15). Previous studies indicate that the accumulation of late embryogenesis abundant proteins and alcohol dehydrogenase (Adh) gene are correlated with stress tolerance [35,36]. The significant up-regulation of LEA and Adh genes in Vagad in drought stress suggests that these genes play an important role in conferring drought tolerance, whereas RAHS-14 tends toward the senescence during drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of them were confirmed to be connected to known biological processes in drought resistance, exhibiting the power of this method in analyzing plant microarray data for studying genotype-phenotype relationships. Similarly, Li et al (2008) reported a cis-regulatory element-based computational approach to genome-wide identification of genes putatively responding to various osmotic stresses in Arabidopsis . With this approach, the 500 top-scoring genes were selected, 91.3% of which were related to the stress response and ABA response in GO enrichment analysis.…”
Section: Physiological and Genetic Studies On Drought Tolerance In Brmentioning
confidence: 99%